2009
DOI: 10.1007/s00404-009-1326-3
|View full text |Cite
|
Sign up to set email alerts
|

Is single umbilical artery an independent risk factor for perinatal mortality?

Abstract: Isolated SUA in our population was noted as an independent risk factor for perinatal mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 12 publications
5
42
1
11
Order By: Relevance
“…The presence of an isolated SUA has also been associated with increased rates of perinatal mortality [15]. In our study population, no case of IUFD or perinatal mortality has been observed.…”
Section: Commentmentioning
confidence: 89%
“…The presence of an isolated SUA has also been associated with increased rates of perinatal mortality [15]. In our study population, no case of IUFD or perinatal mortality has been observed.…”
Section: Commentmentioning
confidence: 89%
“…Based on these findings, some authors have recommended that fetal growth should be monitored throughout pregnancy after prenatal diagnosis of a single umbilical artery. [7][8][9]11,12 As a matter of fact, throughout the study period, our management protocol for pregnancies diagnosed with ISUA included serial follow up fetal growth scans. And when fetal growth restriction was diagnosed additional fetal well being tests were performed.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,11,[13][14][15]18,[20][21][22][23] On the other hand, all post-natal studies have shown that birth weight is significantly lower in ISUA pregnancies compared to control pregnancies. 5,9,10,12 This is possibly related to the fact that these are the studies with greater sample size. Moreover, since ISUA was not diagnosed …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated higher rates of preterm delivery, fetal growth restriction and perinatal mortality (Mart í nez-Payo et al 2005;Murphy-Kaulbeck et al 2010;Hua et al 2010;Burshtein et al 2011). However, Predanic et al (2005) have not found any diff erence in the incidence of smallfor-gestational age newborns between fetuses with isolated SUA and those with a 3-vessel umbilical cord.…”
Section: Introductionmentioning
confidence: 97%